Recommendations for Medical Informatics Training in The Netherlands - Hasman, A. (Methods of Information in Medicine, 1994)
In this contribution recommendations for education and training in Medical Informatics as they have been formulated end 1987 by the Subcommittee Medical Informatics of the Royal Netherlands Academy of Arts and Sciences are described. The current situation of education and training is presented and compared with the recommendations. It is concluded that not all recommendations have yet been followed up.
Keywords: Medical Informatics; education; training; recommendations